Pelatihan pengisian e-Filing - M. Ridwan Tikollah; Samsinar Samsinar (Seminar Nasional Pengabdian Kepada Masyarakat, 2020)
The partner in the implementation of the Community Partnership Program (PKM) was the Faculty of Economics (FE)Universitas Negeri Makassar (UNM). The problems of the partner was the lack of understanding of lecturers and educationalstaff of the partner in filling of e-Filing, so that lecturers and education staff as taxpayers need a long time to fill it out and needhelp from other parties. To overcome this, an e-Filing Training was conducted to provide lecturers and education staff of partnerto be able to fill e-Filing smoothly. The method used includes: lecture, question and answer, and simulation/practice of filling e-Filing. The results achieved were the lecturers and education staff of the partner: (1) having an adequate understanding of fillinge-Filing, and (2) having the ability to complete e-Filing